Living with diabetes in Northeast India: An exploration of psychosocial factors in management - Naphisabet Kharsati; Mrinmoyi Kulkarni (Elsevier, 2024)
Purpose: India is the 'Diabetes Capital of the World' and accounts for one in seven adults living with diabetes worldwide. Psychosocial, economic, and cultural correlates of disease have important implications for disease management but are rarely explored in India. The purpose of this study is to address psychosocial and cultural factors in diabetes management in the northeastern region of India which has a high disease burden. Methods: This study attempts to explore the psychosocial and lived experience of diabetes in the northeastern state of Meghalaya. The sample was selected from individuals attending an outpatient facility of a multi-speciality clinic. Semi-structured interviews were conducted with 25 individuals (13 women and 12 men), above the age of 40 years, who had been diagnosed with diabetes for at least 6 months. The narratives were analysed using thematic analysis. Results: Using the social cognitive framework, themes were organized in terms of a thematic map linking knowledge of diabetes to the perception of diabetes as 'a silent killer', to coping, leading to self-efficacy. However high self-efficacy, over time, may lead to complacency, disrupting health behaviours and requiring re-establishment of those behaviours. Adequate knowledge along with cognitive adaptation and self-efficacy were important constructs that contributed to behaviour change and maintenance. Elements of the cultural context were observed in the spiritual aspects of adaptation, the socially isolating consequences of diabetes, as well as gender differences in social support and management. Conclusion: Understanding the lived experiences of patients contributes to planning more effective interventions keeping the social and cultural context in mind for more effective management of diabetes. Additionally, acknowledging and supporting women's needs in diabetes management is called for.